MONITORING AND CLASSIFICATION OF FIRE HAZARD EVENTS IN VIETNAM DISTRIBUTED FIRE FIGHTING EQUIPMENT SYSTEM - Hoang Ngoc Hai, Ngo Van Nam (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Vietnam is actively trying to become level with the developed countries of Southeast Asia, increasing its investment and tourism attractiveness. Recently, developing also digital opportunities. In this article, a systematic analysis of the fire situation and monitoring of firefighting equipment. The possibility of reducing the complexity of firefighting and decision making is emphasized. It's shown how with the help of fire safety indicators and monitoring data, the fire protection system can be integrated into the digital infrastructure of Vietnam. Key infrastructure transformations of fire monitoring are also indicated. Procedures and criteria for assessment and classification of fire hazardous events are proposed. In particular, evaluation criteria for the sustainability of monitoring have been proposed. System methods, simulations, neural network and fuzzy-multiple apparatus were used. It's shown how to identify the risk index, and then the protection class and technical support using the total network capability to limit the spread of fires.